Transcriptome Profiling of Tomato Uncovers an Involvement of Cytochrome P450s and Peroxidases in Stigma Color Formation - Zhang, Yan; Zhao, Guiye; Li, Yushun; Zhang, Jie; Shi, Meijing; Muhammad, Tayeb; Liang, Yan (Frontiers in Plant Science, 2017)
Stigma is a crucial structure of female reproductive organ in plants. Stigma color is usually regarded as an important trait in variety identification in some species, but the molecular mechanism of stigma color formation remains elusive. Here, we characterized a tomato mutant, yellow stigma (ys), that shows yellow rather than typical green color in the stigma. Analysis of pigment contents revealed that the level of flavonoid naringenin chalcone was increased in the ys stigma, possibly as a result of higher accumulation of p-coumaric acid, suggesting that naringenin chalcone might play a vital role in yellow color control in tomato stigma. To understand the genes and gene networks that regulate tomato stigma color, RNA-sequencing (RNA-Seq) analyses were performed to compare the transcriptomes of stigmas between ys mutant and wild-type (WT). We obtained 507 differentially expressed genes, in which, 84 and 423 genes were significantly up-regulated and down-regulated in the ys mutant, respectively. Two cytochrome P450 genes, SlC3H1 and SlC3H2 which encode p-coumarate 3-hydroxylases, and six peroxidase genes were identified to be dramatically inhibited in the yellow stigma. Further bioinformatic and biochemical analyses implied that the repression of the two SlC3Hs and six PODs may indirectly lead to higher naringenin chalcone level through inhibiting lignin biosynthesis, thereby contributing to yellow coloration in tomato stigma. Thus, our data suggest that two SlC3Hs and six PODs are involved in yellow stigma formation. This study provides valuable information for dissecting the molecular mechanism of stigma color control in tomato.